Change and Continuity in Student Achievement from Grades 3 to 5: A Policy Dilemma - McCaslin, Mary; Burross, Heidi Legg; Good, Thomas L. (Education Policy Analysis Archives, 2005)
In this article, we examine student performance on mandated tests in grades 3, 4, and 5 in one state. We focus on this interval, which we term "the fourth grade window," based on our hypothesis that students in grade four are particularly vulnerable to decrements in achievement. The national focus on the third grade as the critical benchmark in student performance has distracted researchers and policy makers from recognition that the fourth grade transition is essential to our understanding of how to promote complex thinking and reasoning that are built upon a foundation of basic skills that may be necessary, but are not sufficient, for the more nuanced learning expected in subsequent grades. We hypothesized that the basic skills that define a successful third grade performance do not predict successful performance in subsequent years. We examined student performance over time using two measures of student success: the Arizona Instrument to Measure Standards (AIMS), a standards based test; and the Stanford 9 (SAT9), a norm-referenced test. Three groups of schools were included in these analyses. Schools were individually matched to the original sample of interest, which were schools serving students of poverty that received state funding to implement Comprehensive School Reform (CSR) models that emphasize continuity across grade levels. The first comparison sample includes schools that also serve students of poverty but did not receive CSR funding, "nonCSR" schools. The second comparison sample includes schools individually matched on all variables except economic status. These schools, which we term "ow poverty" schools, are the wealthiest public schools in the state, with less than 10% of attending students receiving free or reduced lunch. Student test scores in math, reading, and writing (AIMS) or language (SAT9) were analyzed for the years 2000-2003. These intervals allowed the analysis of two cohorts of the fourth grade window. Our results suggest that the reliance on third grade performance to label students and schools is untenable.